Remote Genetic Counseling and Psychoeducation for Patients with Genetic Issues: a Systematic Literature Review - Setiawan, Henri; Hidayat, Nur; Setiawan, Doni; Firmansyah, Andan; Ariyanto, Heri (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Remote technology refers to electronic information and telecommunication technologies utilized by medical personnel and doctors to manage patient health remotely. Such technologies encompass digital images, videos, or text files stored on computer systems. Technology-driven remote genetic counseling has demonstrated efficacy in enhancing the quality of life for patients afflicted with genetic disorders. Hence, researchers undertook a systematic review to assess the impact of remote technology interventions on the psychological well-being of patients with genetic diseases. Inclusion criteria comprised English articles published from 2012 to 2023 focusing on technology-based remote genetic counseling interventions for patients with genetic disorders, with outcomes pertaining to psychological well-being. Research designs included randomized controlled trials and quasi-experimental studies, while exclusion criteria encompassed literature reviews, systematic reviews, and scoping reviews. The review encompassed four databases: PubMed, Scopus, Proquest, and Wiley. Critical Appraisal Checklist from the Joanna Briggs Institute was employed for methodological assessment. The studies, comprising randomized controlled trials and quasi-experimental designs, met the inclusion criteria. The review of remote genetic counseling and psychoeducational interventions indicated a significant impact on psychological well-being, thereby enhancing the quality of life for patients with genetic disorders. remote genetic counseling  and psychoeducational interventions interventions have been shown to ameliorate the psychological status of patients affected by genetic disorders, thereby enhancing their quality of life. Evidence-based interventions utilizing technology can be integrated into medical care systems to effectively manage patients with genetic disorders. Keywords: Remote Genetic Counseling, Mobile Applications, Psychoeducation, Telephone, Web-Based